Analyzing the Role of Knowledge, Family Influences, and Personality in Shaping Entrepreneurial Behavior - Mutmainah, Arum; Solihat, Asri; Nugraha, Sukma (Entrepreneurship Faculty, Universitas Garut, 2024)
This study aims to examine the influence of entrepreneurial knowledge, family factors, and personality on interest in entrepreneurship among students of the Faculty of Entrepreneurship, Garut University. This study used quantitative with a descriptive approach. The sample used was 201 respondents who were distributed using a questionnaire through Google Forms and processed using the SPSS version 26 statistical application using a simple random sampling technique. The data was analyzed by multiple linear regression analysis and hypothesis testing. The results of the study showed that the Entrepreneurship Knowledge Variable had a significant influence of 13,860 on interest in entrepreneurship; Family factors also have a significant influence on interest in entrepreneurship of 11,943; and personality variables had a significant influence on interest in entrepreneurship of 12,998. Entrepreneurial knowledge variables, family factors, and personality have an influence of 97% on interest in entrepreneurship, and the remaining 3% is influenced by other variables.